The Eye and Eye Diseases from the Perspective of Ancient Babylonian and Biblical Sources: A Study of Selected Texts - Anna Barnau (Acta Medica Martiniana)
Until the late 19th century, the sources of the Hebrew Bible as well as the writings of classical Greco-Roman authors, provided the only information about the history of ancient Mesopotamia, Canaan, and other civilizations of the ancient Near East. It is difficult to determine how much Hebrew ophthalmology depends on the ophthalmology of other nations. It can only be said that the Babylonians and Egyptians had the greatest influence on it. The Jewish ancestor Abraham immigrated from Mesopotamia to Canaan, and Babylonia already had a high culture in the fourth millennium BC, also in relation to medicine in general, and ophthalmology in particular.